Cerebral sinus venous thrombosis during childhood acute lymphoblastic leukemia therapy: Risk factors and management. Issue 12 (29th June 2017) - Ghanem, Khaled M.; Dhayni, Raghida M.; Al‐Aridi, Carol; Tarek, Nidale; Tamim, Hani; Chan, Anthony K. C.; Saab, Raya; Abboud, Miguel R.; El‐Solh, Hassan; Muwakkit, Samar A.
Abstract: Background: Cerebral sinus venous thrombosis (CSVT) is a rare but serious complication of childhood acute lymphoblastic leukemia (ALL) therapy. No available consensus exists regarding its risk factors and appropriate management due to the rarity of cases. Procedures: Out of 209 ALL patients aged 1–21 years treated at the Children's Cancer Center of Lebanon between May 2002 and May 2015, 13 developed CSVT during therapy. Patient characteristics, clinical management, and outcomes were studied. Results: The incidence of CSVT was 6.2% (95% confidence interval [CI]: 3.4–10.4). Using univariate analysis, increased risk of CSVT was observed with age >10 years (odds ratio [OR]: 3.56, 95% CI: 1.13–11.2), T‐cell immunophenotype (OR: 4.14, 95% CI: 1.16–14.7), and intermediate/high risk disease (OR: 3.4, 95% CI: 1.03–11.7). The only statistically significant risk factor by multivariate analysis was the treatment as per the intermediate‐/high‐risk protocol (HR: 15.6, 95% CI: 1.43–171.3). Most cases (77%) occurred in the postinduction phases of treatment while receiving a combination of asparaginase and dexamethasone rather than prednisone. Treatment with low molecular weight heparin (LMWH) for a minimum of 3 months and until significant radiological improvement is observed resulted in 100% survival rate. All but one patient had complete neurological recovery. Conclusions: CSVT is an important complication of childhood ALL therapy. Postinduction combined asparaginase and dexamethasone intensive treatment for intermediate‐/high‐risk patients was the most important risk factor. Treatment with LMWH for a minimum of 3 months, and until asparginase therapy is over, with major radiological improvement seems to be effective and feasible.